Pharmacology of a non-selective ETA and ETB receptor antagonist, TAK-044 and the inhibition of myocardial infarct size in rats. - Watanabe, T (1995)
1. The aims of the present study were to characterize the pharmacological profile of a new endothelin (ET) receptor antagonist, TAK-044 and to consider whether it limits the extension of myocardial infarct size in rats. 2. Binding of [125I]-ET-1 to ET receptors on rabbit ventricular and cerebellar membrane fractions was inhibited by TAK-044 with IC50 values of 3.8 nM and 130 nM, respectively. 3. It inhibited ET-1, ET-2 and ET-3-induced vasoconstriction of porcine isolated coronary arteries in a competitive (ET-1, ET-2) and a non-competitive (ET-3) manner. 4. In the rat in vivo, the ET-1-induced blood pressure changes including transient hypotension followed by sustained hypertension, were inhibited by TAK-044 (0.1-10 mg kg-1, i.v.) in a dose-dependent manner. 5. Acute myocardial infarction induced by 1 h coronary occlusion followed by 24 h reperfusion in rats caused an infarct size of 60 +/- 2% (n = 12) of the area-at-risk by weight. 6. Intravenous injection of TAK-044 10 min before coronary occlusion reduced the infarct size in a dose-dependent manner: 32% and 54% reductions at 1 and 3 mg kg-1, respectively. 7. TAK-044 administered 10 min before or 1 h after reperfusion (1 mg kg-1, i.v.) showed similar inhibitory effects: 34% and 23% reductions, respectively. 8. We conclude that TAK-044 is an ETA/ETB receptor antagonist which shows strong inhibitory effects on the extension of myocardial infarct size after coronary artery occlusion-reperfusion in rats.